Why it's always x !!

Algebra Level 3

If x x + 1 x \frac{1}{x} = 3 \sqrt{3} , then find the value of x 18 x^{18} + x 12 x^{12} + x 6 x^6 +1.


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Pi Han Goh
Oct 6, 2014

Let x = cos θ + i sin θ 1 x = cos θ i sin θ x = \cos \theta + i \sin \theta \Rightarrow \frac {1}{x} = \cos \theta - i \sin \theta

Substitute them into the given equation yields 2 cos θ = 3 θ = π 6 2 \cos \theta = \sqrt3 \Rightarrow \theta = \frac {\pi}{6}

Apply De Moivre's Theorem: x 6 = cos ( 6 θ ) + i sin ( 6 θ ) = 1 x^6 = \cos (6 \theta) + i \sin (6 \theta) =-1 , you should get the desired answer of ( 1 ) 3 + ( 1 ) 2 + ( 1 ) 1 + 1 = 0 (-1)^3 + (-1)^2 + (-1)^1 + 1 = \boxed{0}

Elegant solution, bro! Although, a simpler method would be cubing the given expression to get x 6 + 1 = 0 x^6+1=0 and then finding the required value (say V V ) as,

V = x 18 + x 12 + x 6 + 1 = ( x 6 + 1 ) ( x 12 + 1 ) = 0 ( x 12 + 1 ) = 0 V=x^{18}+x^{12}+x^6+1 = (x^6+1)(x^{12}+1)=0(x^{12}+1)=\boxed{0} .

Prasun Biswas - 6 years, 5 months ago

Smart Solution

Kushagra Sahni - 6 years, 8 months ago
Chew-Seong Cheong
Dec 20, 2014

x + 1 x = 3 ( x + 1 x ) 2 = ( 3 ) 2 x 2 + 2 + 1 x 2 = 3 x+\dfrac {1}{x} = \sqrt{3}\quad \Rightarrow \left( x+\dfrac {1}{x} \right)^2 = \left( \sqrt{3} \right)^2 \quad \Rightarrow x^2 + 2 + \dfrac {1}{x^2} = 3

x 2 + 1 x 2 = 1 x 2 ( x 2 + 1 x 2 ) = x 2 x 4 + 1 = x 2 \Rightarrow x^2 + \dfrac {1}{x^2} = 1 \quad \Rightarrow x^2 \left( x^2+\dfrac {1}{x^2} \right) = x^2 \quad \Rightarrow x^4+1 = x^2

x 2 ( x 4 + 1 ) = x 4 x 6 + x 2 = x 4 x 6 = x 4 x 2 = 1 \Rightarrow x^2 \left( x^4+ 1 \right) = x^4 \quad \Rightarrow x^6 + x^2 = x^4 \quad \Rightarrow x^6 = x^4 - x^2 = -1

x 12 = ( x 6 ) 2 = 1 x 18 = ( x 6 ) 3 = 1 \Rightarrow x^{12} = ( x^6 )^2 = 1 \quad \Rightarrow x^{18} = (x^6)^3 = -1

x 18 + x 12 + x 6 + 1 = 1 + 1 1 + 1 = 0 \Rightarrow x^{18} + x^{12} + x^6 +1 = -1+1-1+1 = \boxed{0}

Rab Gani
Jun 4, 2020

Let The answer is a. Since x is not 0, we can write (x^18+x^12+x^6+1)/x^9 = a/x^9. (x^9 + 1/x^9) + (x^3+ 1/x^3) = a/x^9. Consider (x+1/x)^3 = 3.sqrt.(3), so (x^3 + 1/x^3) + 3(x+1/x) = 3.sqrt.(3), and we find (x^3 + 1/x^3) = 0, and consider (x^3 + 1/x^3)^3 = 0, or (x^9 + 1/x^9) + 3( (x^3 + 1/x^3) = 0, so (x^9 + 1/x^9) =0, we find a/x^9= 0, or a=0

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...